2014
DOI: 10.1017/s0007114514002475
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of leucine on muscle protein synthesis, lean body mass and leg lean mass accretion in older people: a systematic review and meta-analysis

Abstract: In the present study, we performed a meta-analysis to assess the ability of leucine supplementation to increase the muscle protein fraction synthetic rate and to augment lean body mass or leg lean mass in elderly patients. A literature search was conducted on Medline, Cochrane, EMBASE and Google Scholar databases up to 31 December 2013 for clinical trials that investigated the administration of leucine as a nutrient that affects muscle protein metabolism and muscle mass in elderly subjects. The included studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 50 publications
(135 reference statements)
2
78
1
2
Order By: Relevance
“…There is also considerable evidence that different protein sources vary in their capacity to stimulate MPS, with whey protein being more effective than either casein or soy [87]. Supplementation with 20-40 g of high-quality, rapidly digested, leucine-rich protein can improve physical performance in older adults [88], but a number of studies have failed to observe any beneficial effects of protein supplementation alone on muscle probably due to differences in the type, timing, dose and/or distribution of protein intake [89]. While further studies are needed to determine optimal protein supplementation strategies for older adults, a recent consensus statement recommends a daily protein intake of 1.0-1.2 g/kg with at least 20-25 g of high-quality protein at each meal [90].…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…There is also considerable evidence that different protein sources vary in their capacity to stimulate MPS, with whey protein being more effective than either casein or soy [87]. Supplementation with 20-40 g of high-quality, rapidly digested, leucine-rich protein can improve physical performance in older adults [88], but a number of studies have failed to observe any beneficial effects of protein supplementation alone on muscle probably due to differences in the type, timing, dose and/or distribution of protein intake [89]. While further studies are needed to determine optimal protein supplementation strategies for older adults, a recent consensus statement recommends a daily protein intake of 1.0-1.2 g/kg with at least 20-25 g of high-quality protein at each meal [90].…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…Furthermore, in a systematic review and meta-analysis, Leu supplementation was determined to be effective on muscle protein synthesis assessed by FSR, without affecting lean body mass or leg lean mass accretion in elderly patients participating in nine randomized controlled trials. Hence, such therapeutic schemes may be beneficial for elderly with sarcopenia [43]. Recently, Murphy et al documented that, in healthy old subjects, Leu supplementation increased the integrated muscle protein synthesis response [44].…”
Section: Supplementation With Leumentioning
confidence: 99%
“…In humans, the use of Leu alone resulted in increased levels of plasma Leu, ultimately leading to a disproportionate balance for other amino acids. There is no evidence from long-term exposures to high doses of Leu as to how it may affect lean leg mass [43]. Currently, it is not recommended to use Leu alone, especially in long-term elderly supplementation.…”
Section: Leumentioning
confidence: 99%
See 1 more Smart Citation
“…Even when isolated from other essential amino acids, leucine can independently activate mTORC1 (51) and enhance muscle protein synthesis (52). Multiple studies have shown that essential amino acid bolus feedings that include 3 grams of leucine significantly increase muscle protein fractional synthetic rate in older adults (53)(54)(55). In young adults, 10 grams of essential amino acids (~2 grams of leucine) mixed in a noncaloric, noncaffeinated carbonated beverage was sufficient to induce maximal postprandial muscle protein synthesis (56).…”
Section: Leucine-stimulated Protein Synthesismentioning
confidence: 99%